x 1 + y 1 x 1 + z 1 y 1 + z 1 = = = 3 1 5 1 7 1
Given the system of equations above, what is the value of y z ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
very nice using componendo n dividendo loved it
Loved the simplicity of your solution! But how did you get from 2/15 and 1/7 to 14/15? Is that a specific algebraic rule?
Log in to reply
That's the third equation in question (1/y)+(1/z)=(1/7)
"by componendo and dividendo rule" the best part of the best solution
This solution was so dope ;) nice way to solve it!
It is given that:
⎩ ⎪ ⎪ ⎪ ⎪ ⎨ ⎪ ⎪ ⎪ ⎪ ⎧ x 1 + y 1 = 3 1 x 1 + z 1 = 5 1 y 1 + z 1 = 7 1 . . . ( 1 ) . . . ( 2 ) . . . ( 3 )
E q . 1 + E q . 2 − E q . 3 : E q . 3 a → E q . 1 : E q . 3 a → E q . 2 : E q . 2 a E q . 1 a : x 2 = 3 1 + 5 1 − 7 1 = 1 0 5 4 1 2 1 0 4 1 + y 1 = 3 1 2 1 0 4 1 + z 1 = 5 1 y z = 2 9 ⇒ x 1 = 2 1 0 4 1 ⇒ y 1 = 2 1 0 2 9 ⇒ z 1 = 2 1 0 1 . . . ( 3 a ) . . . ( 1 a ) . . . ( 2 a )
Maybe we can lessen our calculation by not calculating for x :)
Did it like that , but without calculating the x
Even did the same!!
⎩ ⎪ ⎪ ⎪ ⎪ ⎨ ⎪ ⎪ ⎪ ⎪ ⎧ x 1 + y 1 = 3 1 x 1 + z 1 = 5 1 y 1 + z 1 = 7 1 . . . ( 1 ) . . . ( 2 ) . . . ( 3 ) ⎩ ⎪ ⎪ ⎪ ⎪ ⎨ ⎪ ⎪ ⎪ ⎪ ⎧ ( 2 ) − ( 1 ) y 1 − z 1 = 1 5 2 . . . . ( 4 ) S u b t r a c t ( 4 ) f r o m ( 3 ) z 2 = 1 0 5 1 . . ( 5 ) A d d ( 3 ) a n d ( 4 ) y 2 = 1 0 5 2 9 . . . ( 6 ) y z = ( 5 ) ( 6 ) = 2 9
this one is superb !
Add the three equations together to get 2 ( x 1 + y 1 + z 1 ) = ( 1 / 3 ) + ( 1 / 5 ) + ( 1 / 7 ) (equation 1 ).Then subtract the 2 ( x 1 + y 1 ) = ( 2 / 3 ) from both sides to get z 2 = ( 7 1 / 1 0 5 ) − ( 7 0 / 1 0 5 ) = ( 1 / 1 0 5 ) , so z = 2 1 0 . Subtract 2 ( x 1 + z 1 ) = ( 2 / 5 ) from both side of equation 1 yields y 2 = ( 7 1 / 1 0 5 ) − ( 4 2 / 1 0 5 ) = ( 2 9 / 1 0 5 ) , so y = ( 2 1 0 / 2 9 ) . It follows that y z = 2 1 0 / 2 9 2 1 0 = 2 9 .
Being (1), (2) and (3) the equations, making (1)-(2)+(3) yields
y 2 = 3 1 − 5 1 + 7 1 = 1 0 5 2 9
and making (1)+(2)-(3) we have
z 2 = 3 1 + 5 1 − 7 1 = 1 0 5 1
Divinding these expressions by one another, we have
2 / z 2 / y = y z = 1 / 1 0 5 2 9 / 1 0 5 = 2 9
Good observation that allows us to eliminate the variables in a smart way!
Equation (1) + (3) - (2) Gives you:
2/y = 29/105
Therefore y = 210/29
Substitute it Equation (3) to give z = 210
z/y = 210/(210/29) = 29
let 1/x = a, 1/y = b, 1/z = c
a + b = 1/3
a + c = 1/5
b + c = 1/7
from equation 1,
b = 1/3 - a
from equation 2,
c = 1/5 - a
substitute these in equation 3
1/3 - a + 1/5 - a = 1/7
-2a = -41/105
a = 41/210
b = 1/3 - 41/210 = 29/210
c = 1/5 - 41/210 = 1/210
Now, solve for x,y and z
1/x = 41/210
x = 210/41
1/y = 29/210
y = 210/29
1/z = 1/210
z = 210
z/y = 210/(210/29)
z/y = (210/1) x (29/210) = 29
Even we can solve by putting 1/x=a 1/y=b 1/z=c Then solve simultaneously for a,b,c And then find b/c!!!!
Problem Loading...
Note Loading...
Set Loading...
x 1 + y 1 − ( x 1 + z 1 ) = 3 1 − 5 1
z y z − y = 1 5 2
similarly z y z + y = 7 1
by dividing z + y z − y = 1 5 1 4
now by Componendo and Dividendo ,
z + y − ( z − y ) z − y + ( z + y ) = 1 5 − 1 4 1 4 + 1 5
2 y 2 z = 1 2 9
hence y z = 2 9